Penerapan Space Syntax pada Konfigurasi Ruang: Analisis Bibliometrik - Nurjanah Ratnaningrum; Ema Yunita Titisari; Antariksa Antariksa (Arsir: Jurnal Arsitektur, 2025)
This study aims to determine and see research opportunities related to the application of spatial syntax to spatial configuration in the scope of architecture. The research method uses bibliometric analysis with the keywords Spatial Syntax and Spatial Configuration in the period 2016-2024 using Mendeley software to collect data and VOSviewer software to visualize the data obtained. The results of data collection using Mendeley contain 75 scientific article data related to spatial syntax and spatial configuration. Meanwhile, the results of image visualization using VOSviewer software show 34 clusters and 184 items (topics) that are interrelated. Bibliometric analysis shows that spatial syntax is closely related to the topics of spatial configuration, urban morphology, and social interaction in architectural science. The development of research on the application of the spatial syntax method to spatial configuration is expected to be carried out in the future through this study.